Optimization of expenditures on environmental actions in Ukraine - Mashchenko, Maryna; Klimenko, Olena; Dykan, Olena (Technology audit and production reserves, 2017)
The necessity of Ukraine transition to developing ecologically safe national economics and limited financial input into the environment preservation have determined the need to optimize the expenditures on securing, reconstructing and recreating the natural environmental potential of the Ukrainian economics. Dynamic analysis of governmental expenditures on environment preservation has been performed via expert assessment method, during which experts have been defined and surveyed, matrix of ranks of the directions in environment preservation has been created, obtained results have been verified with coefficient of multiple ranks correlation and the criteria of results randomness. The performed analysis has allowed to define the most significant directions of the country environment preservation actions from the point of financial input priority. The performed analysis of governmental expenditures on environment preservation is the beginning of long-term research, the main goal of which is the creation of complex methodic of rational environment resources usage. Consequently, the current paper describes the created methodological approach towards environment preservation, one of the most important result of the mentioned approach is the forecast of social, ecological and economical development of Ukraine. All in all, the current paper contains intermediate, even preliminary results that are to be further investigated in the future works.